Saradesāī smāraka grantha - Tikekar, Shripad Ramchandra, 1900-1979 (SAMP early 20th-century Indian books project ;, 1938)
Contributed articles on Maratha history; festschrift honoring Govind Sakharam Sardesai, 1865-1959, Indian historian.